2017
DOI: 10.1002/dvdy.24553
|View full text |Cite
|
Sign up to set email alerts
|

Cellular glycosylation senses metabolic changes and modulates cell plasticity during epithelial to mesenchymal transition

Abstract: Epithelial to mesenchymal transition (EMT) is a developmental program reactivated by tumor cells that leads to the switch from epithelial to mesenchymal phenotype. During EMT, cells are transcriptionally regulated to decrease E-cadherin expression while expressing mesenchymal markers such as vimentin, fibronectin, and N-cadherin. Growing body of evidences suggest that cells engaged in EMT undergo a metabolic reprograming process, redirecting glucose flux toward hexosamine biosynthesis pathway (HBP), which fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 107 publications
(184 reference statements)
1
26
0
Order By: Relevance
“…Our results were in agreement with other studies, showing that HIF-1α is essential for the dynamic transition of breast cancer tumorigenic states (Kuo et al, 2016) and involved in the breast cancer aggressiveness and tumor resistance by epigenetic regulation of glycosylation-related genes Version: Postprint (identical content as published paper) This is a self-archived document from i3S -Instituto de Investigação e Inovação em Saúde in the University of Porto Open Repository For Open Access to more of our publications, please visit http://repositorio-aberto.up.pt/ A01/00 (Greville et al, 2016). In addition, several studies have shown that the morphological changes occurring during EMT are accompanied by a metabolic shift towards glucose metabolism reprograming and aberrant glycosylation (Li and Li, 2015;Lucena et al, 2016;Carvalho et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our results were in agreement with other studies, showing that HIF-1α is essential for the dynamic transition of breast cancer tumorigenic states (Kuo et al, 2016) and involved in the breast cancer aggressiveness and tumor resistance by epigenetic regulation of glycosylation-related genes Version: Postprint (identical content as published paper) This is a self-archived document from i3S -Instituto de Investigação e Inovação em Saúde in the University of Porto Open Repository For Open Access to more of our publications, please visit http://repositorio-aberto.up.pt/ A01/00 (Greville et al, 2016). In addition, several studies have shown that the morphological changes occurring during EMT are accompanied by a metabolic shift towards glucose metabolism reprograming and aberrant glycosylation (Li and Li, 2015;Lucena et al, 2016;Carvalho et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced levels of O -GlcNAcylation diminished the colorectal CSC compartment in vivo by overexpression of the epigenetic regulation of MYB proto-oncogene like 1 (MYBL1), a transcriptional activator of E-cadherin [ 149 ] (Figure 4D ). The key role of O -GlcNAcylation of other EMT actors has also been well highlighted [ 150 , 151 ]. The comprehension of the mechanisms underlying the role of O -GlcNAcylation in cell apoptosis remains at its beginnings.…”
Section: Glycosylation Alterations In Colorectal Cancer Cells and Resmentioning
confidence: 99%
“…N-cadherin is a cell surface adhesion molecule and a major structural element in intercellular adhesion. Its principal function is to mediate cell adhesion and migration ( 32 ). The expression of N-cadherin is increased in epithelial malignant tumors and is associated with the EMT ( 33 ).…”
Section: Discussionmentioning
confidence: 99%